2023
DOI: 10.3389/fphar.2023.1149511
|View full text |Cite|
|
Sign up to set email alerts
|

Could peripheral 5-HT level be used as a biomarker for depression diagnosis and treatment? A narrative minireview

Abstract: The serotonin hypothesis of depression is still influential, but the relationship between peripheral 5-HT levels and depression is still unknown. This review aimed to verify whether peripheral 5-HT levels could be used as a biomarker for depression diagnosis and treatment. PubMed and EMBASE were searched using terms appropriate to the area of research. Articles from 1957 to 2022 in the following terms were identified: depression, 5-HT, serotonin and peripheral (serum, plasma, blood platelets). 33 studies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…SAR studies have shown that the piperidine moiety is essential for pharmacological activity, with superior antidepressant effects observed when the hydroxyl group occurs at the 4th position of the piperidine ring as opposed to the 3rd position. Different studies have reported the antidepressant effects of 3-[5-(aryl [1,3,4]oxadiazole-2-yl]-piperidine derivatives. In this context, FST results have shown that, in comparison with standard drugs such as tiagabine (10 mg/kg) and imipramine (50 mg/kg) or even a control, 10 mg/kg of compounds 16 to 18 (Fig.…”
Section: Piperidinementioning
confidence: 99%
See 1 more Smart Citation
“…SAR studies have shown that the piperidine moiety is essential for pharmacological activity, with superior antidepressant effects observed when the hydroxyl group occurs at the 4th position of the piperidine ring as opposed to the 3rd position. Different studies have reported the antidepressant effects of 3-[5-(aryl [1,3,4]oxadiazole-2-yl]-piperidine derivatives. In this context, FST results have shown that, in comparison with standard drugs such as tiagabine (10 mg/kg) and imipramine (50 mg/kg) or even a control, 10 mg/kg of compounds 16 to 18 (Fig.…”
Section: Piperidinementioning
confidence: 99%
“…[1][2][3] Serotonin (5-hydroxytryptamine, 5-HT), commonly referred to as 5-HT, represents a crucial neurotransmitter that modulates central nervous system activity and peripheral functions through interactions with 5-HT receptors. [4] Decreased serotonin levels in the synaptic gap are closely associated with the onset of depression and can lead to severe mood disorders. [5] Among the 7 different subtypes of 5-HT receptors (5-HT 1 -5-HT 7 ), [6][7][8][9][10] 5-HT 1A receptor has been extensively and intensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…It has been firmly established that chronic stress has a significant impact on the progression of cancer and is closely linked to the gut-brain axis ( Jiang et al, 2023 ; Radford-Smith and Anthony, 2023 ). By regulating the gut microbiota, stress responses in individuals with tumors can be alleviated ( Zhang Z. et al, 2020 ; Kumar et al, 2023 ; Li C. et al, 2023 ). A range of interventions, such as probiotics, prebiotics, postbiotics, and 5-HTP, can effectively achieve this outcome ( Zhang Z. et al, 2020 ; Jiang et al, 2023 ; Kumar et al, 2023 ; Li C. et al, 2023 ; Radford-Smith and Anthony, 2023 ).…”
Section: Targeting Chronic Stress For Enhanced Anticancer Therapiesmentioning
confidence: 99%
“…By regulating the gut microbiota, stress responses in individuals with tumors can be alleviated ( Zhang Z. et al, 2020 ; Kumar et al, 2023 ; Li C. et al, 2023 ). A range of interventions, such as probiotics, prebiotics, postbiotics, and 5-HTP, can effectively achieve this outcome ( Zhang Z. et al, 2020 ; Jiang et al, 2023 ; Kumar et al, 2023 ; Li C. et al, 2023 ; Radford-Smith and Anthony, 2023 ). Moreover, the incorporation of conventional, complementary, and integrative approaches, including acupuncture ( von Trott et al, 2020 ; Han et al, 2021 ; Chen et al, 2023 ), meditation ( Cramer et al, 2017 ; Kinkead et al, 2018 ), herbal medicine (e.g., Si-Ni-San) ( Zhang J. et al, 2023 ) and Tai Chi ( Irwin et al, 2017 ), has demonstrated efficacy in suppressing the proliferation and spread of tumors caused by chronic psychological stress.…”
Section: Targeting Chronic Stress For Enhanced Anticancer Therapiesmentioning
confidence: 99%
“…Reduced anxiety-like behavior and decreased serotonin receptor expression were observed in germ-free mice (Wichers and Maes, 2004). As a major neurotransmitter, 5-hydroxytryptamine (5-HT) can regulate the secretion of opioid peptide, gamma-aminobutyric acid, glutamic acid and other transmitters, and plays a key regulatory role in many aspects of emotion, cognition, substance dependence and so on (Li et al, 2023). More than 95% of body's 5-HT is produced by the enteric nervous system (ENS) (Mayer, 2011) and some species of bacteria, such as Enterococcus, produce 5-HT (Clarke et al, 2014).…”
Section: Introductionmentioning
confidence: 99%